Emotional coping of nursing students during mental health nursing simulation training - Marianne Annion; Merle Ojasoo; Ülle Ernits; Kristi Puusepp (Proceedings of the Estonian Academy of Sciences, 2023)
The process of carrying out simulation training within mental health nursing is part of a teaching method used to increase a studentâs understanding of mental illness, allowing them to develop the required empathic practices that will form part of their skillset. Simulation training has proven to be an effective teaching method within the nursing curriculum. Simulation training provides assistance in the alleviation of societal stigma and general fear and anxiety when communicating with patients who have mental health disorders. The aim of this research is to study student emotions and feelings that may have arisen within the context of mental health simulation training. The current research was conducted by making use of a cohort of undergraduate nursing students in the field of mental health who were undertaking mental health simulation training in a healthcare college. Student feedback was analysed using qualitative content analysis, based on a process of self-reflection by the students themselves. The analysis focused on emotions that had arisen during the study process, and emotional management processes that had been adopted by the students. The results of the research confirmed the supposition that the students had undergone emotional tension during mental health simulation training. Based on the results of the analysis, a model could be designed, which would provide the required emotional preparation and support during a mental health simulation training. This consists of a series of recommendations, which will assist in the emotional preparation of students who are undertaking simulation training.